Indoor rock climbing (bouldering) as a new treatment for depression: study design of a waitlist-controlled randomized group pilot study and the first results - Luttenberger, Katharina; Stelzer, Eva-Maria; Foerst, Stefan; Schopper, Matthias; Kornhuber, Johannes; Book, Stephanie (BMC Psychiatry, 2015)
Depression is one of the most common diseases in industrialised nations. Physical activity is regarded as an important part of therapeutic intervention. Rock climbing or bouldering (rock climbing to moderate heights without rope) comprises many aspects that are considered useful, but until now, there has been hardly any research on the effects of a bouldering group intervention on people with depression. The purpose of this controlled pilot study was twofold: first, to develop a manual for an eight-week interventional program that integrates psychotherapeutic interventions in a bouldering group setting and second, to assess the effects of a bouldering intervention on people with depression.The intervention took place once a week for three hours across a period of eight weeks. Participants were randomly assigned to the two groups (intervention vs. waitlist). The intervention group began the bouldering therapy immediately after a baseline measurement was taken; the waitlist participants began after an eight-week period of treatment as usual. On four measurement dates at eight-week intervals, participants completed the Beck Depression Inventory II (BDI-II), the symptom checklist-90-R (SCL-90), the questionnaire on resources and self-management skills (FERUS), and the attention test d2-R. A total of 47 participants completed the study, and the data were analysed with descriptive statistics. Cohen's d was calculated as a measure of the effect size. For the primary hypothesis, a regression analysis and the Number Needed to Treat (NNT) (improvement of at least 6 points on the BDI-II) were calculated.After eight weeks of intervention, results indicated positive effects on the measures of depression (primary hypothesis: BDI-II: Cohen's d = 0.77), this was supported by the regression analysis with "group" as the only significant predictor of a change in depression (p = .007). The NNT was four.These findings provide the first evidence that therapeutic bouldering may offer an effective treatment for depression. Further research is required.Current controlled trials, ISRCTN17623318 , registered on July 15(th) 2015.
EVALuna2:23684